Relationship between antithrombin activity and interval from diagnosis to delivery among pregnant women with early‐onset pre‐eclampsia. Issue 1 (21st February 2019) - Morikawa, Mamoru; Umazume, Takeshi; Hosokawa‐Miyanishi, Ami; Watari, Hidemichi; Kobayashi, Takao; Seki, Hiroyuki; Saito, Shigeru
Abstract: Objective: To determine the cutoff of antithrombin activity for predicting the interval from diagnosis of early‐onset pre‐eclampsia to delivery. Methods: At Hokkaido University Hospital, Japan, data were retrospectively assessed on antithrombin activity measured at both diagnosis of pre‐eclampsia and delivery among women with singleton pregnancy and pre‐eclampsia (defined by combined gestational hypertension and proteinuria) between 2009 and 2017. The timing of delivery was determined by maternal and fetal well‐being. Results: Among 2904 singleton deliveries, antithrombin activity was measured for 94 (3.2%) women diagnosed with pre‐eclampsia. The median (range) interval was significantly longer for 38 (40%) women with early‐onset than for 56 (60%) women with late‐onset pre‐eclampsia (6.5 [0–27] vs 1 [0–29] days, respectively; P <0.001). In the early‐onset group, median antithrombin activity at diagnosis was significantly lower for 19 women with an interval of less than 7 days (72% [60%–92%]) than for 19 women with a longer interval (≥7 days) (84% [59%–110%]; P =0.012). Antithrombin activity of 78% at diagnosis of early‐onset pre‐eclampsia was optimal for predicting a delivery interval of less than 7 days. Conclusion: A cutoff of 78% antithrombin activity at diagnosis of early‐onset pre‐eclampsia might be used as a predictor of delivery within 7 days. Abstract : An antithrombin activity of 78% or less at diagnosis of early‐onset pre‐eclampsia was found to predict delivery within 7 days.